BUCAL DISEASES WITH SISTEMIC COMPROMISE - Romero Díaz, Manuel H. (2004)
Oral health problems affect the general condition of people. The clinical diagnosis of oral disease can give an idea of the cause and prognosis, but don´t reflect directly the level of individual disturbance. For most people oral diseases are not for long life, not severe enough to disable, but its consequences can impact daily life and cause varying degrees of disability perception altering psychosocial development. There are evidences that oral diseases can significantly impact systemic condition.